The implementation of sport learning at school: Reality and Injury - Ali Satia Graha; Sumaryanto Sumaryanto; Sumaryanti Sumaryanti; Novita Intan Arovah; Rizki Mulyawan (LPMPP Universitas Negeri Yogyakarta, 2023)
A good sport learning planning could minimize injury risk in sports learning. The study aimed at finding out the preparation process of sport learning planning and the number of injury cases. It used a cross-sectional design with a quantitative approach. It was conducted in April-October 2022 at junior high schools in the Special District of Yogyakarta. Its samples were drawn from 20,401 students and 33 physical, sports, and health education teachers using a random sampling technique that gave 400 samples (171 males and 229 females). The validity test of the student questionnaire gave r-count r-table (0.235) and alpha Cronbach of 0.928 0.655, while the validity test of the teacher questionnaire gave r-count r-table (0.344) and alpha Cronbach of 0.737 0.655. Results: There were 158 students (39.50%) who got cervical vertebrae injuries, 193 students (48.25%) who got shoulder injuries, 133 students (33.25%) who got elbow injuries, 182 students (45.50%) who got wrist injuries, 163 students (40.75%) who got finger injury, 198 students (49.50%) who got waist injury, 170 students (42.50%) who got pelvis injury, 202 students (50.50%) who got knee injury, 170 students (42.50%) who got ankle injury, and 165 students (41.25%) who got toe injury. Concerning sports learning planning, there were 2 teachers (6.1%) who never planned sports learning, 8 teachers (24.2%) who rarely planned it, 13 teachers (39.4%) who occasionally planned it, 9 teachers (27.3%) who often planned, and 1 teacher (3.0%) who always planned it. Conclusion: Knee injury was the most common one and teachers have not well-planned sport learning. It was necessary to conduct further study of the correlation between sports learning planning and the injury